2022
DOI: 10.3389/fgene.2022.998147
|View full text |Cite
|
Sign up to set email alerts
|

Integrative pan-cancer analysis and clinical characterization of the N7-methylguanosine (m7G) RNA modification regulators in human cancers

Abstract: Background: RNA modification is one of the epigenetic mechanisms that regulates post-transcriptional gene expression, and abnormal RNA modifications have been reported to play important roles in tumorigenesis. N7-methylguanosine (m7G) is an essential modification at the 5′ cap of human mRNA. However, a systematic and pan-cancer analysis of the clinical relevance of m7G related regulatory genes is still lacking.Methods: We used univariate Cox model and Kaplan-Meier analysis to generate the forest plot of OS, PF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 67 publications
1
5
0
Order By: Relevance
“…Studies have suggested that NUDT4 is signi cantly downregulated in various cancers, including KIRC[57][58][59] , , which matches our results. Research in other cancer types has also indicated that NUDT4 downregulation affects tumor cell proliferation by impacting the m7G gene[60].Research indicates that the absence of certain m7G-related regulatory factors is linked to disease.…”
supporting
confidence: 91%
“…Studies have suggested that NUDT4 is signi cantly downregulated in various cancers, including KIRC[57][58][59] , , which matches our results. Research in other cancer types has also indicated that NUDT4 downregulation affects tumor cell proliferation by impacting the m7G gene[60].Research indicates that the absence of certain m7G-related regulatory factors is linked to disease.…”
supporting
confidence: 91%
“…The association between UPB1 levels and survival outcomes across all cancer types was determined using the Kaplan-Meier plot (http://kmplot.com/analysis/) based on hazard ratios and log-rank P values. Cox univariate regression analysis was used to determine overall survival (OS), disease-specific survival (DSS), disease-free interval, and progression-free interval (PFI) in all cancer samples using the R package “survivalROC.” A P -value of <0.05 was considered to indicate statistical significance, as previously described 18–20 …”
Section: Methodsmentioning
confidence: 99%
“…A P-value of <0.05 was considered to indicate statistical significance, as previously described. [18][19][20] Tumor Immune Estimation Resource (TIMER2.0) Database TIMER2.0 was used to examine the association between UPB1 levels and tumor-infiltrating lymphocytes (TILs) across multiple cancer types based on gene modules. 21 In addition, the association between UPB1 levels and TIL markers, such as CD8 + /CD4 + T cells, B cells, and other related subtypes, was evaluated using correlation modules.…”
Section: Kaplan-meier Plot Analysismentioning
confidence: 99%
“…A study by Han et al demonstrated that m7G tRNA modification drives tumorigenesis through regulating the RPTOR/ULK1/autophagy axis in esophageal squamous cell carcinoma. 12 Recent reports have shown that m7G provides new clues to the clarification of the molecular mechanism of liver cancer and may guide new treatment strategies. 13 Dai et al found that significantly increased m7G tRNA modification and its methyltransferase complex component WDR4 are associated with a poor prognosis of intrahepatic cholangiocarcinoma because they promote carcinogenic mRNA translation and cancer progression.…”
Section: Introductionmentioning
confidence: 99%
“…Great progress has been made in studying the regulation of m7G in cancer. A study by Han et al demonstrated that m7G tRNA modification drives tumorigenesis through regulating the RPTOR/ULK1/autophagy axis in esophageal squamous cell carcinoma 12 . Recent reports have shown that m7G provides new clues to the clarification of the molecular mechanism of liver cancer and may guide new treatment strategies 13 .…”
Section: Introductionmentioning
confidence: 99%